Shakespearian and Quranic literary methods about Characteristics of White and Black Magic - Hameed Abdulameer Hameed Alkhafaji (Zien Journals, 2023)
The struggle between good and evil will go on forever. There are multiple occurrences of this conflict all along the timeline. Furthermore, how these manifestations demonstrate their abilities vary. "Magic" refers to one of the weapons used in that war. The bad guys initially employed magic to further their selfish ends at the expense of the good guys. It's called "Black magic" because it's so evil. The good guys have responded to this magic by developing their brand of magic to counteract the dark arts; they call it "White Magic." When it comes to undoing the damage caused by the evil power, white magic is all about the good guys fixing things. This paper attempts to clarify the nature of magic by comparing two sources: Shakespeare's The Tempest and the story of Harut and Marut, two angels from the Quran. The characters Prospero, Ariel, and Sycorax, who all dealt with magical works "black and white," will be presented in this research paper to provide the main definitions of magic, magical types "white and black," and applications of magic from Shakespeare's final play, The Tempest. The story of the two angels, Harut and Marut, will then be used to present the magical elements of the Quran. The study will also shed light on the Quran's perspective on the "Universal Law of God" (Sunna Takwiniyah) and whether or not it agrees with this principle. The research also looks into the solutions proposed by the Quran to counteract the threat of magic.
Keywords: Quran; Shakespeare; Harut & Marut; Tempest; Magic